2002
DOI: 10.1097/00004728-200203000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Echo Planar Imaging of Ovarian Tumors: Is It Useful to Measure Apparent Diffusion Coefficients?

Abstract: With conventional MRI, a tendency of ADCs could be predicted. ADCs may not provide additional information, especially to discriminate benign from malignant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 18 publications
8
76
1
1
Order By: Relevance
“…For this reason the cystic or necrotic parts of the tumors were not measured in our study. The use of DW-MRI in discriminating between benign and malignant ovarian tumors has been disappointing due to prominent cystic components in this pathology (31).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason the cystic or necrotic parts of the tumors were not measured in our study. The use of DW-MRI in discriminating between benign and malignant ovarian tumors has been disappointing due to prominent cystic components in this pathology (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is considerable overlap between benign and malignant masses in the mentioned parameters (Timmerman et al, 2000;Katayama et al, 2002;Thomassin-Naggara et al, 2009). Researchers in different studies have investigated more recent functional MR techniques such as DCE-MRI, DWI, and its quantitative derivative, ADC in distinguishing benign from malignant adnexal masses (Katayama et al, 2002;Takeuchi et al, 2010;ThomassinNaggara et al, 2011;Li et al, 2012;Zhang et al, 2012). The present study showed that DWI, mean ADC value, and TIC type contribute to differentiating benign from malignant adnexal masses, with TIC type being more accurate than DWI and mean ADC value.…”
Section: Discussionmentioning
confidence: 99%
“…that ADC values are not useful for differentiating benign from malignant adnexal masses (Katayama et al, 2002;Fujii et al, 2008). Thomassin-Naggara et al (2009) demonstrated that DWI signal intensity is an accurate tool for predicting benignity of complex adnexal masses, but ADC measurements did not contribute to differentiating benign from malignant adnexal masses.…”
Section: 3407 Differentiation Of Benign From Malignant Adnexal Massementioning
confidence: 98%
See 2 more Smart Citations